Jahresbericht 1991 - Kunstgesellschaft Luzern. - Kunstmuseum Luzern, Luzern (Luzern : Kunstgesellschaft Luzern, 1992)
Lum, Ken ; Egloff, Anton ; Zaugg, Rémy ; Rockenschaub, Gerwald ; Fabro, Luciano ; Rütimann, Christoph ; Müller, Josef Felic ; Bucher, François ; Graeser, Camille ; etc.
Duits
boek